PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KEINGINAN UNTUK PINDAH DARI PERUSAHAAN (Studi Kasus pada Dealer di Bandarlampung) - Tika Zelin Fitriyana; Fajar Gustiawaty Dewi; Pigo Nauli (Jurnal Akuntansi dan Keuangan (JAK), 2021)
Turnover can also be defined as the movement of workers out of the organization. Turnover refers to the final reality faced by an organization in the form of the number of employees who leave the organization in a certain period, while the desire of employees to move (turnover intentions) refers to the results of individual evaluations regarding the continuation of relationships with the organization that have not been manifested in definite actions to leave the organization. This study aims to determine the effect of Financial Compensation on Turnover Intention, Knowing the effect of Non-Financial Compensation on Turnover Intention and Knowing the effect of Job Satisfaction on Turnover Intention. In this study, sample selection was carried out using purposive sampling method. The purposive sampling method is a sampling technique with certain considerations. The sample in the study was selected using purposive sampling and obtained 65 samples. Based on the research results, financial compensation has no significant positive effect on the dependent variable, namely Turnover intention (Y), non-financial compensation has no effect on the dependent variable, namely Turnover intention (Y) and Job Satisfaction has no effect on the dependent variable, namely Turnover intention.